KERUSAKAN TEGAKAN DAN LIMBAH PEMANENAN HUTAN RAWA PADA KAWASAN SUATU PERUSAHAAN HUTAN DI KALIMANTAN BARAT - Jumalis Thaib (Jurnal Penelitian Hasil Hutan, 1991)
An  investigation   was carried out  at  one swamp  forest  company   in  West Kalimantan.  Timber  stand  conditions  indi cated  by  the  diameter  of  tree  felled  all  of  wich  were  dominant    tree  species  and  the  density   of  all tree species  having diameter   of  20  cm  and  up are as follows:   the  diameter  ranging from  39, 7 to  62,2  cm  with  an average of  51,0  cm  while the  timber  density   ranging from  89  to  164  trees with  an average of  127 trees per  hectare.By  felling  one  tree  for  harvesting  purpose,   it caused  residual  stand  damages  between   0,35  and  1, 7.1  trees  with  an average of  1,04  trees.  This  large range was caused  not  only  by  the distribution   of  timber  stand  but also by  inappropriate felling directions. Logging  waste  that  consisted  of  stump,   clear bole,  branch  and  victimized   trees  with  the  diameter  o/ 10 cm and up were  0,10  m3  (2  %),  0,80  m3  (19  %), 0,16  m3  (4 %) and  0,49  m3  (12%), respectively.   These  wastes Cx n be utilized in the  future   because  the output  of processing  industry  is sawn  timber  only  and  the location  of  log resources area is closed to the saw mill site.